2022
DOI: 10.1136/bmjopen-2021-054869
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with COVID-19 severity among patients on maintenance haemodialysis: a retrospective multicentre cross-sectional study in the UK

Abstract: ObjectivesTo assess the applicability of risk factors for severe COVID-19 defined in the general population for patients on haemodialysis.SettingA retrospective cross-sectional study performed across thirty four haemodialysis units in midlands of the UK.ParticipantsAll 274 patients on maintenance haemodialysis who tested positive for SARS-CoV-2 on PCR testing between March and August 2020, in participating haemodialysis centres.ExposureThe utility of obesity, diabetes status, ethnicity, Charlson Comorbidity In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…It is important to note that the frequency of adverse events was lower than that observed in the general population and no patients required medical support [ 11 ]. However, the median age of the sample analyzed in the present work was higher and the effect of age on the incidence of side effects has already been described in previous studies [ 3 , 13 ]. Moreover, in a study by Polewska and colleagues (2021), adverse events were less frequently observed in dialyzed patients than in the age and sex-matched control group [ 29 ].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…It is important to note that the frequency of adverse events was lower than that observed in the general population and no patients required medical support [ 11 ]. However, the median age of the sample analyzed in the present work was higher and the effect of age on the incidence of side effects has already been described in previous studies [ 3 , 13 ]. Moreover, in a study by Polewska and colleagues (2021), adverse events were less frequently observed in dialyzed patients than in the age and sex-matched control group [ 29 ].…”
Section: Discussionsupporting
confidence: 62%
“…While some authors, including ourselves, could not find an association between these variables and the anti-S-RBD IgG titers [ 24 ], other studies suggest that less comorbidity presence leads to a higher anti-S-RBD IgG titer [ 19 , 23 ]. It is worthy to note that a recent study performed in hemodialysis patients also failed to detect an association between COVID-19 severity and obesity, diabetes, or comorbidity presence [ 3 ], factors that do have an impact on disease severity in the overall population. It appears that these differences are also true for vaccine response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, the relatively old age of our patients could be a determinant of the obtained results. However, the average age of our patients is similar to that of the dialysis population in Europe [ 45 , 46 , 47 ]. Thus, our population can be regarded as representative of a typical HD population.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings indicate that factors such as gender, primary kidney disease diagnosis, and comorbidities did not exhibit statistical significance in hemodialyzed patients when considering vaccination status and mortality, except for age and cardiomyopathy. In the study by Rista et al, higher mortality rates were observed in patients undergoing dialysis for diabetic nephropathy ( p < 0.04) and peripheral vascular disease ( p < 0.01) [ 34 ], in contrast to Selvaskandan et al, who found no association between obesity, diabetes status, ethnicity, or Charlson Comorbidity Index with COVID-19 severity [ 35 ]. Kikuchi et al, in their study, used multivariate analysis to show a significant increase in mortality with prolonged duration of dialysis, without a difference in gender or primary disease [ 36 ].…”
Section: Discussionmentioning
confidence: 99%